Assessment of Liver and Renal Function Tests among patients with typhoid fever in Motta General Hospital, Northwest Ethiopia: A Comparative Cross-Sectional Study - BIRKU GASHAW,; GOBENA DEDEFO,; ABERA ABREHAM,; ABUSH GETANEH,; ANDUALEM BAYIH,; YAZAL ABAY,; MELAKU TSEGAYE,; AMANUEL BAYE4,; GELETA GEMECHU,; WOSHKE WORADE,; MEKDES ALEM,; ABEBE EDAO NEGESSO,; et al. (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Typhoid fever remains an important cause of morbidity and mortality in developing countries with poor hygienic conditions and limited access to safe drinking water. It primarily has an impact on the liver and the kidney organs which causes liver and renal function test to be affected. And now, this study was to evaluate liver and renal function tests in typhoid fever patients at Motta General Hospital Northwest Ethiopia, May to December 2023. Method: Hospital-based comparative cross-sectional study was conducted in Motta General Hospital on 90 typhoid fever patients and 90 control groups were selected by convenience sampling technique. Data was analyzed by SPSS version 26 after collecting all clinical and laboratory data. Statistical significance was defined as a p-value < 0.05. Result: The average age of the typhoid fever cases was 32.23± 13.48 years, and control subject was 32.62±7.708. Serum aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total bilirubin, direct bilirubin and creatinine values were significantly higher among typhoid fever patients than control groups. Conclusion: Typhoid fever appeared to significantly affect liver function tests (ALT and AST, ALP, TB and DB) and renal function tests (creatinine) compared to controls. Abnormal liver and renal functions tests in typhoid fever is more common with patients presenting in 2nd and 3rd week of illness. Keywords: Typhoid fever, Liver function tests, Renal function tests